The role and importance of the anti-corruption compliance control system in strengthening anti-corruption measures in state organizations is the key to transparency ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The role and importance of the complaence control system in the field of battling corruption in state organizations and the rules governing the relations that make up its activities, the law and other regulatory acts aimed at organizational and legal regulation of the complaence control system, as well as the impact of corruption on state governing bodies and the effect of introducing a complaence control system